Analisis Penerapan Smart Contract dalam Transaksi Saham di Pasar Modal Syariah Berbasis Blockchain - Sasti Amar Sabila; Sochimin Sochimin (Pusat Riset dan Inovasi Nasional, 2025)
The application of blockchain technology and smart contracts in Islamic capital markets presents significant opportunities to enhance efficiency, transparency, and compliance with Sharia principles in stock transactions. This study investigates the feasibility of implementing smart contracts in Sharia-compliant stock trading within a blockchain-based framework. Using a qualitative descriptive-analytical approach, this study examines the suitability of smart contract mechanisms with Islamic financial principles, evaluates improvements in operational efficiency, and identifies challenges in its implementation. The results show that smart contracts can significantly reduce transaction costs, eliminate intermediary risks, and ensure sharia compliance automatically through programmable rules. However, its implementation faces challenges such as regulatory framework, technology scalability, and stakeholder education. This study presents a comprehensive framework for integrating blockchain technology in Islamic capital markets while maintaining compliance with Sharia principles.